2019
DOI: 10.1096/fj.201802534rr
|View full text |Cite
|
Sign up to set email alerts
|

The immunoregulatory effects of CD8 T‐cell–derived perforin on diet‐induced nonalcoholic steatohepatitis

Abstract: The liver is a central immunologic organ with a high density of myeloid and lymphoid immune cells that play important roles in the development and progression of nonalcoholic steatohepatitis (NASH). However, the immune‐cell–mediated regulation of NASH and its underlying mechanisms remain obscure. In this study, Prf1null mice showed significantly higher plasma alanine transaminase levels, with increased liver fat accumulation, lobular inflammation, and focal necrosis compared with wild‐type (WT) mice after 4 wk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 33 publications
0
33
0
Order By: Relevance
“…PRF1 encodes the protein perforin, which is present in T and NK cells and facilitates the release of granzymes and subsequent cytolysis of target cells ( 61 ). CCR5, CXCL10, CXCR3, CXCL9, CCL5, and IFNG also participate in the migration, trafficking, or differentiation of T cells ( 61 65 ). Whether ETV7 binds the promoter of these genes and stimulates their expression remains unknown, but our analysis showed a high correlation between them and ETV7 at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…PRF1 encodes the protein perforin, which is present in T and NK cells and facilitates the release of granzymes and subsequent cytolysis of target cells ( 61 ). CCR5, CXCL10, CXCR3, CXCL9, CCL5, and IFNG also participate in the migration, trafficking, or differentiation of T cells ( 61 65 ). Whether ETV7 binds the promoter of these genes and stimulates their expression remains unknown, but our analysis showed a high correlation between them and ETV7 at the transcriptional level.…”
Section: Discussionmentioning
confidence: 99%
“…258 Other studies have shown that Tc cell-derived perforin participates in the mechanism regulating liver inflammation and thus plays a protective role in the development of NASH. 259 In addition, a recent study revealed that Tc cells interact synergistically with NKT cells to promote the progression of NASH and increase the incidence of NASH-related HCC. 257 NKT cells.…”
Section: Microbial Dysbiosis and Intestinal Barrier Functionmentioning
confidence: 99%
“…Perforin has also been reported to play critical roles in promoting inflammation-mediated diseases, including type 1 diabetes (33), cerebral malaria (34), and viral myocarditis (35). A recent study revealed that perforin expressed in CD8 T cells regulates innate and adaptive immunity in the liver and exerts a protective effect in MCD (methionine/choline-deficient diet) diet-induced NASH models (36). Interestingly, MCD dietinduced non-obese NAFLD displays characteristics distinct from those of obesity-induced NAFLD.…”
Section: Figure 4 |mentioning
confidence: 99%